The Canadian Rebellions of 1837 and 1838 as a Borderland War: A Retrospective - Dunning, Tom (Ontario History, 2009)
Historians of Southwestern United States history and culture have created the concept of a borderland to explain the historical circumstances of the area where Anglo-America ran into Hispanic America. Its application to the Upper Canada-Great Lakes area during 1837-1838 will allow a re-interpretation of the Canadian Rebellions of 1837 and the subsequent invasions of 1838 as part of a borderland war. Hopefully this approach will eliminate any tensions over the nationalist component of the Canadian Exiles or American Patriot Hunters. I also want to focus on the Battle of Prescott or the Windmill as the significant event of this borderland war, relying on the writings of two of the Exile narrativists, William Gates and Stephen Wright. Finally I hope to contribute some reflections on the significance of these Exiles/Patriots after almost twenty years of an acquaintance of sort with them.